Pengaruh Belanja Modal terhadap Pendapatan Asli Daerah dan Dampaknya Pada Kinerja Keuangan Pemerintah Daerah (Studi Empiris Pada Pemerintah Daerah Kabupaten/Kota Di Provinsi Aceh) - Darwanis Darwanis; Ryanda Saputra (Jurnal Dinamika Akuntansi dan Bisnis, 2014)
The research aims to analyze the influence of Capital Expenditure on the original income and its impact on Local Government Financial Performance This research refers to a previous research’s conducted by Fajar Nugroho (2012). Objects of this research are the entire district and city in Aceh province. The research was carried out by the method of documentation. The data used are secondary data, which comes from the realization of the Budget Report Revenue and Expenditure of the district and the city in Aceh province from 2009 until 2012. The results of this study indicate that the Capital Expenditures negatively affect of the region's financial performance directly, whereas indirect positive effect on Capital Spending Growth through Revenue Financial Performance as an intervening variable region. The results of this study indicate that the capital expenditureeffect on the Local original income, Local original income effect on financial performance, capital expenditures does not affect on the financial performance directly, while indirectly capital expenditureeffect on financial performance through local original income.